Mere addition and the separateness of persons - Rendall, Matthew (Journal of Philosophy, 2015)
How can we resist the repugnant conclusion? James Griffin has suggested that part way through the sequence we may reach a world—let us call it “J”— in which the lives are lexically superior to those that follow. If it would be better to live a single life in J than through any number of lives in the next one (“K”), we may judge the smaller world preferable, as if aggregating the lives in the larger world intrapersonally. I argue that the mere addition paradox arises because adding new people with separate preferences renders such lexical rankings untenable. Whereas in comparing J and K we could legitimately infer that the former was lexically preferable, we cannot “suspend addition” when comparing J+ and K. Instead, for half of these worlds’ populations, it will be preferable to move to K. When one ranking suspends addition and the other does not, the result is an intransitive value judgement: J < J+ < K < J, producing the mere addition paradox.